Sex steroid metabolism and actions in non-small cell lung carcinoma. Issue 193 (October 2019) - Asavasupreechar, Teeranut; Chan, Monica S.M.; Saito, Ryoko; Miki, Yasuhiro; Boonyaratanakornkit, Viroj; Sasano, Hironobu
Highlights: Association sex steroid actions including estrogen, estrogen intracrinology, progesterone, hormone replacement therapy and androgen in NSCLC. Association sex steroid receptor actions including estrogen receptor, progesterone receptor and androgen receptor in NSCLC. Association sex steroid receptor signaling pathway in NSCLC. The possible treatment of NSCLC patients by modulating sex steroid signaling. Abstract: Despite recent development in targeted therapies, lung cancer still remains the leading cause of cancer death. Therefore, a better understanding of its pathogenesis and progression could contribute to improving the eventual clinical outcome of the patients. Results of recently published several in vitro and clinical studies indicated the possible involvement of sex steroids in both development and progression of non-small cell lung carcinoma (NSCLC). Therefore we summarized the reported clinical relevant information of the sex steroids, their receptors and steroid metabolizing enzymes related to NSCLC in this mini-review. In addition, we also reviewed the potential "endocrine therapy", targeting sex steroid actions and/or metabolism in NSCLC patients.